Voluntary sensemaking: the identity formation process of volunteers in sport organizations. Issue 5 (20th October 2019) - Wegner, Christine E.; Jones, Gareth J.; Jordan, Jeremy S.
ABSTRACT: Research question: Volunteers are essential to the management of nonprofit community sport organizations (CSOs). Although previous research has focused on the individual or institutional factors that influence volunteerism in these contexts, there has been less attention to how these factors collectively impact group identity formation, which is associated with collective solidarity. Research methods: Using the theoretical lens of identity work, this case study analyzes this process from a critical realist perspective. Document analysis and a focus group with three paid staff members were used to generate data on the 'sensebreaking' and 'sensegiving' cues projected by a CSO, and interviews were conducted to understand volunteers' 'sensemaking' of these cues, along with the corollary influence on group identity formation. Results and findings: Results indicate reconciling sport identities and adjusting to formalized tasks were salient 'sensebreaking' cues. Moreover, the reputation of the CSO and establishment of role identities were identified as key 'sensegiving' mechanisms, while symbols and conviviality among volunteers helped promote collective group identities. Implications: The discussion focuses on the theoretical implications of findings, focusing specifically on the identity work performed by volunteers and group identity formation, and also discusses key implications for practice.